Estimation of Sialic Acid and IL10 Levels in Stage 1 and 2 Periodontitis Patients - Sudhir Rama Varma; Biju Thomas; Amitha Ramesh; Suchetha Kumari; Shahira; Zainab Abdullah Muhammad Al Saadi; Rabia Asif Mahmood (International Journal of Dentistry)
Objective. The role of biomarkers in staging and grading periodontal disease has become detrimental in relation to the overall treatment plan. This study aimed at evaluating and comparing the role of sialic acid and IL10 in the early and moderate stages of periodontitis. Materials and Methods. Patients were selected according to the assessment of pocket depth and radiographic bone loss. Bone loss was calculated as <15% for stage 1 and 15–33% for stage 2. Salivary samples were collected using spit technique 2 hrs post consumption of food. The unstimulated saliva was collected in a sterile graduated container every minute for 5–8 minutes. IL10 estimation was done using ELISA, and sialic acid estimation was done using the diphenylamine method. The variables for the three groups were assessed using ANOVA, and intragroup comparisons for quantitative data were evaluated using the post hoc Bonferroni test (P<0.05). Results. On comparing sialic acid levels among the three groups, stage 2 showed the highest mean (8.61) compared with the other two groups and was highly significant (P<0.001). On the contrary, IL10 when compared to stage 1 and 2 periodontitis revealed insignificant change. Conclusion. The value of IL10 was higher as patients progressed from health to periodontitis.